(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2023)
Gender-based violence in Brazil is increasingly affecting more and more women. They see their lives destroyed, physically and psychologically as a result of aggression, which often caused by their own family members and partners. And as in all other areas of society, the press also plays a fundamental role in raising awareness about reporting and warning about the seriousness of this scenario. What we often see, however, are factual stories, without the necessary depth and produced by journalists unprepared to talk about this issue. In order to understand how daily journalism on the internet deals with violence against women, this investigation analyzed articles on this topic in five sections of the Brazilian portal G1 in 2017. The editorials related to Brazilian states were chosen because Roraima, Goiás, Mato Grosso, Rondônia and Espírito Santo are the most violent states for women to live in, according to a research by Ipea (Institute for Applied Economic Research). We analyzed their sources and whether the content is produced with a humane approach.